2022
DOI: 10.3390/plants11111508
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Biochemical, and Proteomic Analyses to Understand the Promotive Effects of Plant-Derived Smoke Solution on Wheat Growth under Flooding Stress

Abstract: Wheat is an important staple food crop for one-third of the global population; however, its growth is reduced by flooding. On the other hand, a plant-derived smoke solution enhances plant growth; however, its mechanism is not fully understood. To reveal the effects of the plant-derived smoke solution on wheat under flooding, morphological, biochemical, and proteomic analyses were conducted. The plant-derived smoke solution improved wheat-leaf growth, even under flooding. According to the functional categorizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In flooding conditions, the energy to maintain plant vitality mainly relies on the ethanol-metabolic pathway in glycolysis to degrade glucose and glycogen accompanied by ATP generation [ 24 ]. Under flooding stress, a plant-derived smoke solution enhanced wheat growth; and FBA/GAPDH among glycolysis, which increased under flooding, decreased with its application under the same condition [ 25 ]. In this study, FBA was accumulated in root/leaf under flooding; and its accumulation was recovered to the control level in irradiated wheat ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In flooding conditions, the energy to maintain plant vitality mainly relies on the ethanol-metabolic pathway in glycolysis to degrade glucose and glycogen accompanied by ATP generation [ 24 ]. Under flooding stress, a plant-derived smoke solution enhanced wheat growth; and FBA/GAPDH among glycolysis, which increased under flooding, decreased with its application under the same condition [ 25 ]. In this study, FBA was accumulated in root/leaf under flooding; and its accumulation was recovered to the control level in irradiated wheat ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the modulated proteins, fructose‐bisphosphate aldolase, the key enzyme of glycolysis and gluconeogenesis, was strongly upregulated (Komatsu et al . 2022). A similar pattern was observed in model plants subjected to flooding (Khatoon et al .…”
Section: Discussionmentioning
confidence: 99%
“…2012; Komatsu et al . 2022) and in Acanthus mollis and A. ilicifolius (Liu & Zheng 2021). In these studies, the authors suggested that plants acclimate to chronic hypoxic stress by activating glycolysis and gluconeogenesis to generate energy for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope labelling by/with amino acids in cell culture (SILAC) and isobaric tags for absolute and relative quantification (iTRAQ) seem to be more sophisticated techniques that may monitor changes in the specific kinase domain. So far, various proteomic studies revealed abiotic stress tolerance of the plant, such as in drought [ 167 , 168 ], heat [ 158 , 169 ], chilling [ 159 , 170 ], salinity [ 156 , 171 ] and waterlogging [ 172 , 173 ]. Comparative proteome analysis for Medicago sativa cv.…”
Section: Proteomicsmentioning
confidence: 99%